PENGARUH KEPEMIMPINAN, KEMAMPUAN MANAJERIAL DAN MOTIVASI TERHADAP KINERJA TENAGA PENJUALAN PADA CV. GITA MANDIRI GOWA - Tamrin Meda (AkMen JURNAL ILMIAH, 2017)
This study aims to analyze (1) Effect of leadership, managerial ability and motivation partially on the performance of the sales force; (2) The effect of leadership, managerial ability and motivation simultaneously on the performance of the sales force. This study is a population of the entire sales and non-sales personnel CV. Gita Mandiri Gowa totaling 32 people. Month study period December 2015 to February 2016. The data was collected using questionnaires, interviews and documentation. Methods of data analysis in this study using multiple regression analysis. Data collected were analyzed using the t test and F test results showed that (1) There is a significant and positive influence among the leadership of the performance (value T calculated at 7.784 is greater than t table of 2.045 and 0.0000 significance); (2) There is a significant and positive influence among the managerial capacity of the performance (value T count equal to 2,591 bigger than t table of 2.045 and significance 0.015); (3) There is no significant and positive effect of motivation on performance (value T calculated at 0.353 is greater than t table of 2.045 and 0.727 significance greater than 0.05) .; (4) There is a significant and positive influence among the leadership, managerial ability and motivation together on the performance (value calculated at 104.557 T is greater than t table of 3.340 and 0.000 significance). The factors that most affect the performance is leadership while not influential factor is motivation.